Aspiring to Citizenship: African Immigrant Youth and Civic Engagement in Cape Town, South Africa - Kuah, Alison Sing Yee (African Cinema Unit, 2023)
Based on ethnographic fieldwork carried out in the city of Cape Town over four months, this dissertation addresses the question how do African immigrant youth experience life and live as ‘citizens 'in Cape Town? African immigrant youth straddle multiple positions, localities and identities: insider, outsider, victim, perpetrator, dependent, independent, child, adult. This dissertation examines the various ways in which African immigrant youth in Cape Town activate citizenship and belonging through civic participation or engagement, often in the absence of formal citizenship. Contrary to claims of immigrant youth as inherently problematic, youth are actively deciding to be the change they want to see in the world surrounding them, looking backwards and forwards to determine their decision to participate in civic engagement in the present. This thesis posits that young people's notions of themselves and their aspirations (both individual and collective) impact not only their future life-goals and dreams, but can manifest and drive their current actions to embed themselves in their communities and contribute towards the betterment or improvement of these communities. Drawing from youth studies that highlight the individual agency of youth within the larger constraints in which they find themselves in, the dissertation looks at the everyday, informal and localised acts of civic participation, as well as the ways that African immigrant youth leverage institutions (higher education, community organisations) as bridges and platforms for social change. The research demonstrates that civic participation through community engagement allows African immigrant youth to dream and access citizenship and social adulthood, and become a part of society where they are recognised as contributing members.